PGC‐1α regulates myonuclear accretion after moderate endurance training. Issue 1 (28th July 2021) - Battey, Edmund; Furrer, Regula; Ross, Jacob; Handschin, Christoph; Ochala, Julien; Stroud, Matthew J.
Abstract: The transcriptional demands of skeletal muscle fibres are high and require hundreds of nuclei (myonuclei) to produce specialised contractile machinery and multiple mitochondria along their length. Each myonucleus spatially regulates gene expression in a finite volume of cytoplasm, termed the myonuclear domain (MND), which positively correlates with fibre cross‐sectional area (CSA). Endurance training triggers adaptive responses in skeletal muscle, including myonuclear accretion, decreased MND sizes and increased expression of the transcription co‐activator peroxisome proliferator‐activated receptor‐γ coactivator‐1α (PGC‐1α). Previous work has shown that overexpression of PGC‐1α in skeletal muscle regulates mitochondrial biogenesis, myonuclear accretion and MND volume. However, whether PGC‐1α is critical for these processes in adaptation to endurance training remained unclear. To test this, we evaluated myonuclear distribution and organisation in endurance‐trained wild‐type mice and mice lacking PGC‐1α in skeletal muscle (PGC‐1α mKO). Here, we show a differential myonuclear accretion response to endurance training that is governed by PGC‐1α and is dependent on muscle fibre size. The positive relationship of MND size and muscle fibre CSA trended towards a stronger correlation in PGC‐1a mKO versus control after endurance training, suggesting that myonuclear accretion was slightly affected with increasing fibre CSA in PGC‐1α mKO. However, in larger fibres, the relationship between MND and CSA was significantly altered in trained versus sedentary PGC‐1α mKO, suggesting that PGC‐1α is critical for myonuclear accretion in these fibres. Accordingly, there was a negative correlation between the nuclear number and CSA, suggesting that in larger fibres myonuclear numbers fail to scale with CSA. Our findings suggest that PGC‐1α is an important contributor to myonuclear accretion following moderate‐intensity endurance training. This may contribute to the adaptive response to endurance training by enabling a sufficient rate of transcription of genes required for mitochondrial biogenesis. Abstract : In the present study, we aimed to test whether PGC‐1α is necessary for remodelling myonuclear number, myonuclear domain (MND) sizes and nuclear morphology after endurance training. To this end, we investigated the effects of moderate‐intensity endurance training on myonuclear distribution, organisation and shape in tibialis anterior muscle of wild‐type mice and mice lacking PGC‐1α in skeletal muscle. We found PGC‐1α governs scaling of both MND and myonuclear number with fibre CSA in larger muscle fibres of endurance‐trained mice, suggesting that PGC‐1α regulates myonuclear accretion in larger muscle fibres following endurance training